2008
DOI: 10.1186/1471-2210-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Dicholine salt of succinic acid, a neuronal insulin sensitizer, ameliorates cognitive deficits in rodent models of normal aging, chronic cerebral hypoperfusion, and beta-amyloid peptide-(25–35)-induced amnesia

Abstract: Background: Accumulated evidence suggests that insulin resistance and impairments in cerebral insulin receptor signaling may contribute to age-related cognitive deficits and Alzheimer's disease. The enhancement of insulin receptor signaling is, therefore, a promising strategy for the treatment of age-related cognitive disorders. The mitochondrial respiratory chain, being involved in insulinstimulated H 2 O 2 production, has been identified recently as a potential target for the enhancement of insulin signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 67 publications
7
25
0
4
Order By: Relevance
“…Previously reported effects of DS on increased levels of hippocampal IGF-2, brain N-acetylaspartate/creatine, choline acetyltransferase activity (Storozheva et al, 2008; Cline et al, 2012) can attest for the here observed memory preserving effects of DS. Interestingly, choline acetyltransferase activity in the brain was shown to be regulated by neuronal insulin receptor-mediated mechanisms (Hoyer, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Previously reported effects of DS on increased levels of hippocampal IGF-2, brain N-acetylaspartate/creatine, choline acetyltransferase activity (Storozheva et al, 2008; Cline et al, 2012) can attest for the here observed memory preserving effects of DS. Interestingly, choline acetyltransferase activity in the brain was shown to be regulated by neuronal insulin receptor-mediated mechanisms (Hoyer, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Although both ligands are endogenous to the brain, they are common metabolites and it is presently unclear whether they could serve a physiological role, acting at native mGlu1 receptors. Consistent with the current findings on the cytoprotective properties of succinate, it was shown previously to ameliorate cognitive defects in a rat model of Alzheimer's disease (Storozheva et al, 2008). These compounds may now be used as lead structures in the design of new biased agonists, and especially antagonists, with the ability to affect mGlu1 receptor-mediated protective signaling without disturbing classic G protein-mediated signal transduction.…”
Section: Downloaded Fromsupporting
confidence: 71%
“…In the studies reported here cell viability was quantified using calcein AM/EthD-1 double staining (Figure 1A). Using the MTT assay, an indicator of mitochondrial activity, we confirmed that ceramide treatment of HCSF caused mitochondrial dysfunction, a likely cause of the loss of cell viability (Figure 1B) [23], [24].…”
Section: Resultsmentioning
confidence: 88%